(untitled) (National Administration Journal, 2021)
This work is the result of the analysis and evaluation of what human talent management represents in the current work environment. The main goal is to set a new way of viewing management, starting from a bibliographic review of human resources management, and its evolution through time, highlighting the importance of its transformation, going through organizational progress, and concluding that a change in human talent management its required, in order to increase the strategical support, it can bring to organizational goals achievement.